Characteristics of Suppressor Macrophages Induced by Mycobacterial and Protozoal Infections in relation to Alternatively Activated M2 Macrophages. (15th May 2012) - Tomioka, Haruaki; Tatano, Yutaka; Maw, Win Win; Sano, Chiaki; Kanehiro, Yuichi; Shimizu, Toshiaki
Abstract : In the advanced stages of mycobacterial infections, host immune systems tend to change from a Th1-type to Th2-type immune response, resulting in the abrogation of Th1 cell- and macrophage-mediated antimicrobial host protective immunity. Notably, this type of immune conversion is occasionally associated with the generation of certain types of suppressor macrophage populations. During the course of Mycobacterium tuberculosis (MTB) and Mycobacterium avium-intracellulare complex (MAC) infections, the generation of macrophages which possess strong suppressor activity against host T- and B-cell functions is frequently encountered. This paper describes the immunological properties of M1- and M2-type macrophages generated in tumor-bearing animals and those generated in hosts with certain microbial infections. In addition, this paper highlights the immunological and molecular biological characteristics of suppressor macrophages generated in hosts with mycobacterial infections, especially MAC infection.